Europe for dummies - Bramblett, Reid (New Jersey, 2005)
Lively and engaging, this invaluable handbook puts the continent's great cities and regions at your fingertips, and includes all the highlights plus the very best off-the-beaten-path experiences that make any visit to Europe memorable. Packed with experienced insider tips, Europe For Dummies offers: Essential information on London, Edinburgh, Dublin, Paris, Amsterdam, Munich & the Bavarian Alps, Vienna, Prague, Rome, Florence & Tuscany, Venice, Barcelona, and Athens A select choice of favorite hotels and eateries in every destination and price category Indispensable foreign language
Keywords: Europe; Europe Guidebooks; Travel